Probing prefrontal cortex hemodynamic alterations during facial emotion recognition for major depression disorder through functional near-infrared spectroscopy - Gao, Lin; Cai, Yunli; Wang, Huaning; Wang, Gang; Zhang, Quan; Yan, Xiangguo (Journal of neural engineering, 2019)
Objective. A serious issue in psychiatric practice is a lack of specific, objective biomarker to assist clinicians in establishing differential diagnosis and improving individualized treatment. Major depression disorder (MDD) is characterized by poorer ability in processing of facial emotional expressions. Approach. Applying a portable neuroimaging system using near-infrared spectroscopy, we investigated the prefrontal cortex hemodynamic activation changes during facial emotion recognition and rest periods for 27 MDD patients compared with 24 healthy controls (HC). Main results. The hemodynamic changes in the left prefrontal cortex for the MDD group showed significant differences in the median values and the Mayer wave power ratios of the oxygenated hemoglobin (oxy-Hb) and deoxygenated hemoglobin (deoxy-Hb) during the emotional face recognition compared with the HC subjects, indicating the abnormal oxidative metabolism and weaker local hemodynamic oscillations for the MDD. The mean cross wavelet coefficients and the average wavelet coherence coefficient between oxy-Hb and deoxy-Hb over the left prefrontal cortex, and also between the bilateral oxy-Hb in the MDD patients were significantly lower than the HC group, demonstrating abnormal locally functional connectivity over the left prefrontal cortex, and the inter-hemispheric connection between the bilateral prefrontal cortices. Significance. These results suggested that the hemodynamic changes over the left prefrontal cortex and between the bilateral prefrontal cortices detected by fNIRS could provide reliable predictors for the diagnosis of the depression in clinic, and also supported the rationale for use of transcranial magnetic stimulation over the left dorsolateral prefrontal cortex to restore excitability of prefrontal cortex that exhibits diminished regulation of emotion-generative systems in the MDD patients.